Regional Corridors Development in Regional Cooperation - Pradeep Srivastava (Asian Development Bank (ADB), 2011)
Regional corridors are popular components of regional cooperation initiatives and have been in use for several years. Yet discussion about development of these corridors tends to be relatively general in scope and difficult to pin down in terms of content and implications. This paper elaborates on a simple framework for regional corridors development in the context of regional cooperation, anchored on two dimensions of these corridors: the extent to which they are national or regional and the area of their utilization. The framework is subsequently applied to the Greater Mekong Subregion (GMS) regional cooperation program, yielding several implications for its future. The GMS program needs to redefine what constitutes a regional project and to formulate a regional master plan for further development of GMS regional corridors. The framework is also applied toward identifying an appropriate methodology for monitoring performance of regional corridors.
hdl:11540/2029
Keywords: O18; R12; 330; Economic geography; Urbanization; Regional; Regional Corridors; Regionale Wirtschaftsintegration; Handelsliberalisierung; Grenzüberschreitender Verkehr; Internationale Zusammenarbeit; Greater Mekong